2020
DOI: 10.1038/s41746-020-00327-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of therapist-guided Internet-delivered cognitive behavior therapy for pediatric obsessive-compulsive disorder

Abstract: Cognitive behavior therapy (CBT) is the recommended first-line intervention for children and adolescents with obsessive-compulsive disorder (OCD), but is not broadly accessible. Internet-delivered CBT (ICBT) with minimal therapist support is efficacious and cost-effective, at least in the short term. Whether the therapeutic gains of ICBT for OCD are sustained in the long run is unknown. In this study, 61 adolescents with OCD who participated in a randomized trial of ICBT were followed-up 3 and 12 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…It is possible that the 3 months to follow-up measurement frequently chosen in studies is too short and that further reductions in OCD symptoms do not become significant until after this time. Our own results, in addition to those of other studies ( 26 , 61 ), support this interpretation. Therefore, the question of the follow-up periods required for internet-based treatments to fully capture the long-term treatment effects should be further explored.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that the 3 months to follow-up measurement frequently chosen in studies is too short and that further reductions in OCD symptoms do not become significant until after this time. Our own results, in addition to those of other studies ( 26 , 61 ), support this interpretation. Therefore, the question of the follow-up periods required for internet-based treatments to fully capture the long-term treatment effects should be further explored.…”
Section: Discussionsupporting
confidence: 91%
“…In essence, ICBT mimics traditional in-person CBT in terms of content, the only difference being the mode of delivery ( Hedman et al, 2012 ). The safety, efficacy, durability and cost-effectiveness of ICBT for children and adolescents for OCD have been well established ( Aspvall et al, 2018 ; Lenhard and Andersson, 2017 ; Lenhard et al, 2014 ; Aspvall et al, 2021 ; Lenhard et al, 2020 ; Lenhard et al, 2017 ). A recent study demonstrated non-inferiority of ICBT compared to in-person CBT for OCD when delivered in a stepped-care fashion ( Aspvall and Andersson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This low-intensity intervention has demonstrated efficacy and cost-effectiveness in 3 open studies 15 , 16 , 17 and 1 randomized waitlist clinical superiority trial. 18 , 19 , 20 In a subsequent randomized noninferiority clinical trial, 19 , 20 152 children and adolescents with OCD were randomly assigned to receive either internet-delivered CBT or in-person CBT during a 16-week period. At the 3-month follow-up, nonresponders in both groups were offered additional in-person CBT sessions.…”
Section: Introductionmentioning
confidence: 99%
“…This study formally tested this hypothesis via a health economic evaluation of our noninferiority trial, as prespecified in the study protocol. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation